A survey of the Collection. - Beeren, W.A.L. (Amsterdam : Stedelijk Museum Amsterdam, 1989)
Abrakanowicz, Magdalena ; Abramovic, Marina & Ulay ; Andre, Carl ; Appel, Karel ; Beckmann, Max ; Beeke, Anthon ; Belskii, Anatoli ; Bickerton, Ashley ; Braque, Georges ; Breitner, George Hendrik ; Cézanne, Paul ; Chagall, Marc ; Constant ; Copier, A.D. ; Corneille ; Couzijn, Wessel ; Cucchi, Enzo ; Czerniawski, Jerzy ; Daniels, René ; Deacon, Richard ; Dekkers, Ad ; Delaunay, Robert ; Dibbets, Jan ; van Doesburg, Theo ; Dubuffet, Jean ; van Elk, Ger ; van der Elsken, Ed ; Ernst, Max ; van Eyk, Ria ; Riverhead (New York) ; Fontana, Lucio ; Gispen, Willem H. ; van Gogh, Vincent ; González, Julio ; Grapus ; Guston, Philip ; Haring, Keith ; Heyboer, Anton ; Johns, Jasper ; Jorn, Asger ; Judd, Donald ; Kandinsky, Wassily ; Kelly, Ellsworth ; Kiefer, Anselm ; Kienholz, Edward ; Kirchner, Ernst Ludwig ; Klein, Yves ; Koch, Pyke ; van Koningsbruggen, Rob ; de Kooning, Willem ; Koons, Jeff ; Kounellis, Jannis ; Kruyder, Herman ; Laurens, Henri ; Lebeau, Chris ; van Leersum, Emmy ; Leger, Fernand ; Lichtenstein, Roy ; Lissitzky, El ; Lord, Andrew ; Louis, Morris ; Lucebert ; Malevich, Kasimir ; Man Ray ; Manet, Edouard ; Marden, Brice ; de Maria, Walter ; Matisse, Henri ; Merz, Mario ; Miro, Joan ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Monet, Claude ; Nauman, Bruce ; Newman, Barnett ; Oldenburg, Claes ; Paik, Nam June ; Penone, Giuseppe ; Perez, Asela M. ; Picasso, Pablo ; Polke, Sigmar ; Raetz, Markus ; Rauschenberg, Robert ; Richier, Germaine ; Rietveld, Gerrit ; Ryman, Robert ; Salvo ; de Sand, Rambow Lienemeyer van ; Sandberg, Willem ; Saura, Antonio ; Schnabel, Julian ; Schoonhoven, Jan ; Schwitters, Kurt ; Serra, Richard ; Severini, Gino ; Sherman, Cindy ; Smit, Robert ; Soutine, Chaim ; Spoerri, Daniel ; Steinbach, Haim ; Stella, Frank ; Struycken, Peter ; etc.
Engels
boek